STRUKTUR DAN FUNGSI SOSIAL CERITA RAKYAT BATU BAIMPIK DI NAGARI PARAMBAHAN SOLOK - Subma Dewita; Muhammad Ismail Nasution (Jurnal Bahasa dan Sastra, 2019)
This article aims to describe: (1) The folklore structure of local legends of Baimpik Stone, (2) social function of local folklore legend of Baimpik Stone in Nagari Parambahan of Bukit Sundi District of Solok. This type of research is qualitative research using descriptive methods. Data gathered from informant through two stages, namely: (1) The recording phase of local folklore legend Baimpik Stone, (2) The stage of data collection about the storytelling environment. Data on the storytelling environment is gathered with recording, observation, and interview techniques. The data in this study was analyzed in four phases, namely: (1) data identification phase, (2) phase of data classification or analysis, (3) stage of discussion and the conclusion, (4) the level of reporting.  Based on the results of the study can be concluded that the folklore structure of local legends of Baimpik Stone in Nagari Parambahan Bukit Sundi District Solok consists of: (1) language style, (2) Point of View, (3) Figure and character, (4) background, the background of the local legend of the folklore of the Baimpik Stone is a backdrop of place, background, and social background, (5) plot/plot, Groove/plot in the folklore of local legend Baimpik Stone is a conventional groove, and has three stages namely, early stage Introductions, middle stage or midle, and final stage or breakout, (6) Themes, and (7) orders. Social function folklore local legend of Baimpik Stone in Nagari Parambahan Bukit Sundi District Solok: (1) entertain, (2) Educate, (3) bequeath, and (4) traditions.